Impact of a community respiratory service on emergency hospital admissions. (13th November 2019) - Levin, K; Anderson, D; Milligan, M; Crighton, E
Abstract: Background: A community respiratory service was implemented in the North West of Glasgow in January 2013, comprising a team of physiotherapists, occupational therapists and support workers, to provide education, self-management advice, and, where appropriate, treatment at home, for COPD patients, to reduce the risk of hospital admission. This study measures the impact of the service on emergency admission to hospital. Methods: COPD EAs were defined as emergency admissions to hospital with a primary diagnosis of COPD. Rate of COPD EAs per 1000 population aged 65 years+ in Glasgow City was compared before and after onset of the service, using segmented linear regression with 21-month pre- and 17-month post-intervention periods. COPD EAs for residents of South and North East Glasgow (S+NE) - areas with no such service in place - were used as a comparison group. The model adjusted for the rate of all-cause emergency admissions. Autoregressive terms were included in the model, as well as a fourier term to adjust for seasonality. Models were similarly run for outcome emergency admissions with COPD in any of the other five fields of diagnosis. Results: Adjusting for all cause EAs and changes in S+NE, thus factoring out the impact of other initiatives that may have affected emergency admission to hospital, the impact of the service was found to be a level change of -0.33 (-0.51, -0.16) and a trend change of -0.03 (-0.05, -0.02) COPD EAs per 1000 per month. This is equivalent to a predicted reduction due to the service of -0.88 COPD EAs per 1000 popn per month, in March 2015, and a relative reduction of 35.8%. Rate of COPD EAs per month reduced over time after the introduction of the service (from the point of full staffing). Rate of EAs with COPD in a field of diagnosis other than primary saw no significant change in level or trend associated with the service. Conclusions: The community respiratory service was associated with a significant reduction in the rate of COPD EAs. Key messages: The Community Respiratory service was associated with reductions in emergency hospital admissions with COPD as a primary diagnosis. There was no significant change in emergency admissions with COPD as a secondary diagnosis, suggesting hospital attendance for patients with COPD overall reduced following the intervention.